The impact of project portfolio management on information technology projects - DE REYCK, Bert (Institutional Knowledge at Singapore Management University, 2005)
The ever-increasing penetration of projects as a way to organise work in many organisations necessitates effective management of multiple projects. This has resulted in a greater interest in the processes of project portfolio management (PPM), with more and more software tools being developed to assist and automate the process. Much of the early work on PPM concentrated on the management of IT projects, largely from the perspective of the management of resources and risk. Many of the recent articles have been by vendors of the software, promoting the value of the PPM process. However, the claims made in those articles are typically only supported by anecdotal evidence. In this paper, we assess whether there is a correspondence between the use of PPM processes and techniques, and improvements in the performance of projects and portfolios of projects. Based on our findings, we introduce a threestage classification scheme of PPM adoption, and present a strong correlation between (1) increasing adoption of PPM processes and a reduction in project related problems, and (2) between PPM adoption and project performance